2017
DOI: 10.1016/j.rbmo.2017.06.021
|View full text |Cite
|
Sign up to set email alerts
|

PTGS2 down-regulation in cumulus cells of infertile women with endometriosis

Abstract: A deleterious effect of endometriosis on oocyte quality has been proposed. Evidence suggests that cumulus cells could be used as indirect biomarkers of oocyte quality. The PTGS2 gene, which encodes cyclooxygenase 2 (COX-2), is deregulated in endometriotic lesions and plays a crucial role in the acquisition of oocyte competence. To date, research evaluating PTGS2 expression in cumulus cells of infertile patients with endometriosis has not been conducted. The aim this study was to compare the expression levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 60 publications
0
14
0
2
Order By: Relevance
“…PTGS2, involved in muscle contraction, was observed to be highly downregulated as well. Its low levels of expression may be involved in infertility [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…PTGS2, involved in muscle contraction, was observed to be highly downregulated as well. Its low levels of expression may be involved in infertility [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized study, Cruz and colleagues (2017) showed that the type of gonadotropin used during controlled ovarian stimulation (follicle-stimulating hormone (FSH), urinary FSH, or human menopausal gonadotropin (hMG)) induce differential gene expression in human CCs [ 50 ]. Moreover, PTGS2 was shown to be down-regulated in CCs of infertile women with endometriosis [ 51 ]. Patient age affects differential mRNA gene expression in CCs [ 52 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…JOSD1 depletion can lead to severe apoptosis in gynaecological cancer cells both in vivo and in vitro (29). The PTGS2 gene, which encodes cyclooxygenase 2 (COX-2), is deregulated in endometriotic lesions and plays an important role in the acquisition of oocyte competence (30). IRAK is responsible for the regulation of microbial colonization of tumors and STAT3 protein stability in tumor cells, leading to tumor cell proliferation (31).…”
Section: Cre Induces Up-and Down-regulation Of Gene Expression Inmentioning
confidence: 99%